Pseudoreplication in Tropical Forests and the Resulting Effects on Biodiversity Conservation - BENJAMIN S. RAMAGE; DOUGLAS SHEIL; HANNAH M.W. SALIM; CHRISTINE FLETCHER; NUR‐ZATI A. MUSTAFA; JOANN C. LURUTHUSAMAY; RHETT D. HARRISON; ELIZABETH BUTOD; AHMAD DZAMIR DZULKIPLY; ABD RAHMAN KASSIM; MATTHEW D. POTTS (Conservation Biology, 2013)
Tropical forest ecosystems are threatened by habitat conversion and other anthropogenic actions. Timber production forests can augment the conservation value of primary forest reserves, but studies of logging effects often yield contradictory findings and thus inhibit efforts to develop clear conservation strategies. We hypothesized that much of this variability reflects a common methodological flaw, simple pseudoreplication, that confounds logging effects with preexisting spatial variation. We reviewed recent studies of the effects of logging on biodiversity in tropical forests ( n = 77) and found that 68% were definitively pseudoreplicated while only 7% were definitively free of pseudoreplication. The remaining proportion could not be clearly categorized. In addition, we collected compositional data on 7 taxa in 24 primary forest research plots and systematically analyzed subsets of these plots to calculate the probability that a pseudoreplicated comparison would incorrectly identify a treatment effect. Rates of false inference (i.e., the spurious detection of a treatment effect) were >0.5 for 2 taxa, 0.3–0.5 for 2 taxa, and Pseudoreplicación en Bosques Tropicales y Efectos Resultantes Sobre la Conservación de Biodiversidad

Optimized Floating Refugia: a new strategy for species conservation in production forest landscapes - Benjamin S. Ramage; Justin Kitzes; Elaina C. Marshalek; Matthew D. Potts (Biodiversity and Conservation, 2013)